1995
DOI: 10.1073/pnas.92.3.768
|View full text |Cite
|
Sign up to set email alerts
|

Induction of vascular endothelial growth factor expression by hypoxia and by glucose deficiency in multicell spheroids: implications for tumor angiogenesis.

Abstract: Perfusion insufficiency, and the resultant hypoxia, often induces a compensatory neovascularization to satisfy the needs of the tissue. We have used multicellular tumor spheroids, simulating avascular microenvironments within a clonal population of glioma tumor cells, in conjunction with in situ analysis of gene expression, to study stress inducibility of candidate angiogenic factors. We show that expression of vascular endothelial growth factor (VEGF) is upregulated in chronically hypoxic niches (inner layers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
276
2
8

Year Published

1996
1996
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 523 publications
(297 citation statements)
references
References 24 publications
11
276
2
8
Order By: Relevance
“…We also observed elevated expression of the protein phosphatase DUSP1, which is upregulated during conditions of oxidative stress and heat shock. 12 Vascular endothelial growth factor (VEGF) also participates in stress responses 13 and showed higher expression levels after overnight incubation of blood. Other known stress-response genes found to be upregulated during overnight shipment included TGF-beta-inducible early growth response gene (TIEG) and growth arrest and DNA-damage-inducible alpha (GADD45A) and beta (GADD45B).…”
Section: Resultsmentioning
confidence: 99%
“…We also observed elevated expression of the protein phosphatase DUSP1, which is upregulated during conditions of oxidative stress and heat shock. 12 Vascular endothelial growth factor (VEGF) also participates in stress responses 13 and showed higher expression levels after overnight incubation of blood. Other known stress-response genes found to be upregulated during overnight shipment included TGF-beta-inducible early growth response gene (TIEG) and growth arrest and DNA-damage-inducible alpha (GADD45A) and beta (GADD45B).…”
Section: Resultsmentioning
confidence: 99%
“…In all xenografts, equally high levels of VEGF mRNA were found, independent of the VEGF expression in the parental cell line (Potgens et al, 1995). Similarly, in xenografted tumours in nude mice in vivo, concomitantly with invasion of new blood vessels and restoration of normoxia in the implanted tumour, VEGF expression was gradually down-regulated to a constitutive low level of expression, representing the output of non-stressed tumour cells (Shweiki et al, 1995). Expression of VEGF in our series did not correlate with the primary melanoma thickness, microvessel density or patient survival in metastatic disease; this may be a reflection of the same phenomenon when hypoxia and possibly also other factors regulate the expression of VEGF in a reversible manner.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the previous smaller series (Stockhammer et al, 2000), we found a strong correlation of VEGF with CSF lactate and a less stronger correlation with CSF albumin. The correlation with CSF lactate makes sense in that lactate may reflect the metabolism of tumour cells in a low-oxygen environment which in turn induces VEGF expression in tumour cells (Shweiki et al, 1995;Fukumura et al, 2001;Ziemer et al, 2001). In fact, acidic pH itself induces VEGF expression (Fukumura et al, 2001).…”
Section: Discussionmentioning
confidence: 99%